An Innovative 12-step Paper Writing Strategy Utilizing Modern Principles of Scientific Writing for Enhancing Successful Outcomes - Das, R.; Das, P. N. (Indian Journal of Nursing Sciences, 2024)
Most PGs today do not even write a paper from their thesis and of the few who do, most follow the procedure blindly, unaware of its basic principles. The chances of successful outcomes in their paper writing venture culminating in its acceptance, is, therefore, not surprisingly, likely to be very low and the reason for it is simply because knowledge and skills necessary for it are neither taught in biomedical institutions nor are resources on it available easily, covering the issue in its entirety. A paper was, therefore, felt necessary to cover all aspects of paper writing, beginning with the crucial preparatory work, and culminating in the post-submission phase do’s, to help our PGs/young researchers achieve best outcomes in their paper writing venture. This paper provides the reader with an innovative 12-step paper writing strategy and primes them on Preparatory work, Journal selection and on writing the paper outline. It also discusses modern principles for composing methodology, results, and discussion, including paragraph construction and provides the reader with suggestions on the relative length of individual sections and sequence in which they need to be written. Finally, it also deliberates on principles to be followed for title, abstract, introduction, and keywords helps decide authorship and guides them to write the all crucial cover-note to editor. It is expected that knowledge contained in this paper, if applied, is likely to generate a quality manuscript which would be hard for the editor/peer-reviewer to reject.